RBC Properties Pte Ltd v Defu Furniture Pte Ltd [2014] SGCA 62: Restatement of Law Relating to Misrepresentation in Singapore - GOH, Yihan (Institutional Knowledge at Singapore Management University, 2014)
The recent Court of Appeal decision of RBC Properties Pte Ltd v Defu Furniture Pte Ltd [2014] SGCA 62 (“RBC Properties”) contains an invaluable restatement of the law relating to misrepresentation in Singapore. This entry aims only to summarise that restatement of law. The interested reader may find the facts of the case succinctly discussed by the Court of Appeal in its judgment here and also in this blog entry on the High Court decision.